Polinización asistida en el cultivo de guanábana “Annona muricata” en el Ecuador - Suarez Aguilar, Luis Fernando (2023)
Soursop (Annona muricata) is a small tree belonging to the Anonáceas family, which are more acceptable for consumption in juice. As with desserts and preserves, they are desired for their flavor; It has antirheumatic, antioxidant, body properties, considered diuretic, anticancer, anti-inflammatory, antibacterial. Pollination is a profitable activity in soursop cultivation since it is directly reflected in the number of fruits produced. It is known that the transfer of pollen from the male part of a flower to the female part of the same or another flower is an important process to maintain the life and genetic diversity of flowering plants, improve the quality, quantity of seeds, fruits and offspring characteristics. Artificial pollination is the procedure used to obtain seed trees, with outstanding characteristics in terms of production, earliness, quality, and resistance to diseases or pests; which consists of the spraying of pollen to the receptive female inflorescences, tending to obtain optimal fertilization and consequently, the increase in productivity in the first years of harvest.